The Impact of Problem- oriented Reporting Education on Characteristics of Nursing Report - M Hemmati Maslakpak; N Khajeali; N Kazemi (Iran University of Medical Sciences, 2013)
Abstract   Background & Aim: Nursing report has been considered as a framework and an important means for providing and evaluating nursing care. The aim of this study was to determine the effect of educating problem-oriented reporting on the characteristics of nursing report.   Material & Methods: This quasi-experimental study was done on the nurses in Urmia Seiyedolshohada and Taleghani hospitals. Nurses with bachelor's degree in nursing (n=60) were first recruited by convenience sampling method and then nurses in Seiyedolshohada hospital (n=30) and Taleghani hospital (n=30) were randomly assigned to experimental or control groups respectively. Problem-based reporting workshop was held for experimental group. Data was collected with a checklist and analyzed by descriptive statistics, t-test and chi-square using SPSS-PC (v. 16).   Results: The findings showed a significant difference between the mean scores of nursing report of morning, afternoon and night shifts, between experimental and control groups after intervention (P<0.05). The results of Independent t-test showed a significant difference between the mean scores of total nursing report between experimental and control groups after intervention (P<0.0001).  Conclusion: According to the findings, educating problem-based reporting has positive impact on the characteristics of nurse reporting. Accordingly using this method by nurses is suggested. Received: 30 Sep 2013 Accepted: 17 Dec 2013